Optimization of the methane production in batch anaerobic digestion of maize straw by adjustment of total solid and substrate-to-inoculum ratio based on kinetics - Zhen, Feng; Xing, Tao; Li, Lianhua; Sun, Yongming; Zhang, Hongqiong (International Journal of Agricultural and Biological Engineering, 2024)
Anaerobic digestion (AD) operating under conditions of organic overload stress typically exacerbates the potential for process instability, thereby resulting in significant economic and ecological ramifications. In this investigation, an augmented substrate-to-inoculum ratio (S/I) along with varying total solid content (TS) levels was employed to replicate diverse organic loadings, utilizing maize straw and cattle manure. The findings reveal that a moderate augmentation in S/I and TS proves advantageous in augmenting methane yield, while an excessive substrate loading diminishes methane yield, hampers the kinetics of methane production, and even induces severe process instability. Kinetic study also displayed the variation of the model parameters for the first-order model, the modified Gompertze model, and the transfer function model. Both the modified Gompertze model and transfer function model exhibited the same environmental stress trend. Thus, both the increase in particulate content and the increase in S/I had a substantial effect on the substrate conversion rate to methane. Microbial analysis demonstrates the dominant influence of Firmicutes and Methanosarcina under different organic loading stresses. From both a kinetic and a microbiological point of view, this work provides novel insights into the fundamental processes that regulate anaerobic digestion (AD) under varying loading stress. Furthermore, it has significant implications for improving the operating efficiency of AD, which is a significant benefit. Keywords: maize straw, dry anaerobic digestion, methane production, microbial characteristics, kinetic model DOI: 10.25165/j.ijabe.20241701.8434 Citation: Zhen F, Xing T, Li L H, Sun Y M, Zhang H Q. Optimization of the methane production in batch anaerobic digestion of maize straw by adjustment of total solid and substrate-to-inoculum ratio based on kinetics. Int J Agric & Biol Eng, 2024; 17(1): 225-231.